Findings from within-subjects comparisons of drug use and sexual risk behaviour in men who have sex with men in England. (March 2017) - Melendez-Torres, GJ; Hickson, Ford; Reid, David; Weatherburn, Peter; Bonell, Chris
Epidemiological evidence for the encounter-level association between sexualised drug use and unprotected anal intercourse in men who have sex with men is unclear and has not examined men who have sex with men in England. To estimate this association, we compared dyadic sexual encounters within respondents. We used encounter-level data from a longitudinal online survey of men who have sex with men living in England and multilevel models to test univariate and multivariate associations between any respondent or partner drug use, specific respondent drug use, additional situational characteristics and unprotected anal intercourse. Based on 6742 encounters from 2142 men who have sex with men, respondent drug use and respondent use of certain specific drugs were associated with increased unprotected anal intercourse odds. In univariate models, partner drug use was associated with increased unprotected anal intercourse odds, but in multivariate models, only non-specific knowledge of partner drug use was associated with the same. Encounters with non-regular-and-steady partners or that were not HIV-seroconcordant were associated with decreased unprotected anal intercourse odds. This is the first within-subjects comparison of drug use and unprotected anal intercourse conducted on a sample from England, and the largest of its kind. Findings are consistent with other studies, though associations between drug use and unprotected anal intercourse are shaped by social contexts that may change over time.